Acute Fatty Liver of Pregnancy (AFLP): A Case Report - Yustisa Sofirina Harahap; Sidharta Kusuma Manggala (Jurnal Sehat Indonesia (JUSINDO), 2026)
Acute fatty liver of pregnancy (AFLP) is a rare but life-threatening obstetric emergency that typically occurs during the third trimester and may lead to acute liver failure in pregnant women. Maternal and fetal mortality rates are substantially increased without prompt diagnosis and treatment; therefore, early recognition and immediate intervention are essential. This case report describes a 34-week pregnant woman who was admitted to the hospital with complaints of nausea, vomiting, heartburn, weakness, and jaundice. Laboratory examinations revealed signs of acute liver failure, including hypoglycemia, elevated liver enzymes, hyperbilirubinemia, severe coagulopathy with disseminated intravascular coagulation (DIC), and thrombocytopenia. The diagnosis of AFLP was established based on the Swansea criteria, with the patient fulfilling ≥6 criteria. The patient was managed in the intensive care unit (ICU), where stabilization was achieved through oxygen therapy, glucose infusion, electrolyte correction, transfusion of blood components, including fresh frozen plasma (FFP) and platelets, to manage DIC, vitamin K administration, and broad-spectrum empirical antibiotic therapy. Once stabilized, an emergency cesarean section was performed at 34 weeks of gestation to prevent further disease progression. The infant was delivered with a birth weight of 2,450 g and Apgar scores of 3 and 5, requiring admission to the neonatal intensive care unit (NICU). Following delivery, the mother’s condition gradually improved, with liver function and coagulation parameters showing improvement within 3–4 days and approaching normal levels within 1 week. Both the mother and infant recovered and were discharged home in good condition.